The Different of News Story and Editorial Texts in Jakarta Post through the Process and Circumstance of Textual Meta-Functions - Lubis, Siti Isma Sari; Rambe, Armita Novriana (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This paper focused on the textual meta-functions to demonstrate the ways in which a news story text and an editorial to find out the percentages of Process and Circumstance in the news story text and editorial text, what is the dominant type of process used, and why new story item is different from editorial item. For purposes of demonstration, it has been chosen two different texts, a news story text and an editorial piece from The Jakarta Post. We use these to analyze the ways in which a reporter and an editorialist make choices in the meta-function component through process and circumstance. Based on the analysis above, the dominant type of process used in the NST (News Story Text) is material with the number of percentage is 33 %, while in ET (Editorial Text) is material process with the number of percentage is 38%. Meanwhile, the dominant type of circumstance used in the NST (News Story Text) is contingency with the number of percentage is 45.5%, while in ET (Editorial Text) is location with the number of percentage is 54%.